Manual for obstetrics and gynecology practitioners - Pandit, Suchita N.; Wani, Reena J. (Jaypee, 2015)
It has been found that in day-to-day practice, there are common clinical situations and scenarios that the practitioner encounters but often there is no clear-cut consensus on what should be done for the given situation. Hence there was a need to come up with a handbook of standard investigation and treatment protocols which can be applied in practice. This should serve as a ready reckoner which can help quick decision making in common situations, and as a guide to what should be done when things do not go well.